2008
DOI: 10.1002/mrm.21654
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of dispersion and pulsatility of blood flow in pulsed arterial spin labeling

Abstract: Arterial spin labeling (ASL) is a method of using MRI to image cerebral perfusion. For the measurement to be calibrated, a model is required describing the kinetics of the flow of the inverted blood from the labeling region to the imaging region. It is common to assume plug-flow, but alternatives such as a Gaussian distribution of arrival times have also been suggested. In this study a physiologically based model for dispersion is developed and compared to existing models when fit to experimental data. The mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 20 publications
(34 reference statements)
1
59
1
Order By: Relevance
“…31, 32 A number of models have been suggested to correct for this, for instance by introducing a Gaussian distribution of tag arrival times at the imaging voxel, and assuming parabolic flow in major arteries. 33 As the temporal width of the d M curve seems to increase with age, particularly in the PCA territory, it would appear that the labeled blood bolus is becoming more dispersed with increasing age, and these models would therefore become particularly relevant in this vascular territory. Furthermore, this natural increase in bolus dispersion with increasing age should be accounted for when assessing changes in T in the presence of pathologies in future clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…31, 32 A number of models have been suggested to correct for this, for instance by introducing a Gaussian distribution of tag arrival times at the imaging voxel, and assuming parabolic flow in major arteries. 33 As the temporal width of the d M curve seems to increase with age, particularly in the PCA territory, it would appear that the labeled blood bolus is becoming more dispersed with increasing age, and these models would therefore become particularly relevant in this vascular territory. Furthermore, this natural increase in bolus dispersion with increasing age should be accounted for when assessing changes in T in the presence of pathologies in future clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Future work could address cardiac effects on this DynAngio because this is an area in the literature that is developing. 19,20 We found significant differences between patients and controls, such as the number of detected voxels in the right and left MCAs. Differences in vascular anatomy and the fact that the cohorts were not equally matched for age and sex may have influenced the results.…”
mentioning
confidence: 78%
“…The effects of bolus dispersion on CBF and ATT estimation with ASL have been studied [29] and modeled [30]; blood dispersion was not included in CBF and ATT in this work. Wu et al [29] concluded that intervoxel flow dispersion dominates intra-voxel flow dispersion, suggesting that modeling laminar flow may not have an appreciable effect on results.…”
Section: G the Effect Of Blood Dispersionmentioning
confidence: 99%
“…Wu et al [29] concluded that intervoxel flow dispersion dominates intra-voxel flow dispersion, suggesting that modeling laminar flow may not have an appreciable effect on results. Gallichan et al [30] proposed a model to account for laminar flow of the labeling bolus which leads to a smoother signal curve, free of discontinuities at the onset and the peak of the perfusion signal curve. This approach would be beneficial to our analysis, however, with only six time points (as was used here) the benefit would not be as great as for data with more time points.…”
Section: G the Effect Of Blood Dispersionmentioning
confidence: 99%